2018
DOI: 10.1016/j.socscimed.2017.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Supportive environments for physical activity in deprived communities in the United Kingdom: A qualitative study using photo elicitation

Abstract: The health benefits of regular physical activity are substantial and well-established. However, population activity levels are insufficient to obtain health benefits in the United Kingdom (UK), and strategies to increase activity, particularly in income-deprived communities, are sought. Socioecological models of physical activity posit that activity levels are influenced by social, physical and wider environmental factors. In line with a growing evidence base, there is a need to understand the factors that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Other literature has underscored the role of cumulative risk in child maltreatment, demonstrating the interactions between multiple pathways in a broader risk environment (Evans et al, 2013; Cicchetti et al, 1997; Molnar et al, 2016). In addition, similar to those who have posited social contacts as a mechanism behind the relation between green space and health (e.g., Maas et al, 2009; Sawyer et al, 2018), our findings suggest that social interaction and relationships may constitute another pathway between certain aspects of the built neighborhood environment—recreation centers, playgrounds, parks—and child maltreatment. These findings add an important dimension to research that has demonstrated the link between the built environment and social capital (Cohen, Inagami, and Finch, 2008; Leyden, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Other literature has underscored the role of cumulative risk in child maltreatment, demonstrating the interactions between multiple pathways in a broader risk environment (Evans et al, 2013; Cicchetti et al, 1997; Molnar et al, 2016). In addition, similar to those who have posited social contacts as a mechanism behind the relation between green space and health (e.g., Maas et al, 2009; Sawyer et al, 2018), our findings suggest that social interaction and relationships may constitute another pathway between certain aspects of the built neighborhood environment—recreation centers, playgrounds, parks—and child maltreatment. These findings add an important dimension to research that has demonstrated the link between the built environment and social capital (Cohen, Inagami, and Finch, 2008; Leyden, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…This mechanism of internalizing or embodying one’s physical surroundings – “you are what your environment is”— highlights a diffuse, yet powerful, way in which the neighborhood built environment could inform both intra- and interpersonal relations. The quality of the built environment was seen as reciprocally shaping individual and social behavior (Sawyer et al, 2018). The caregiver who suggested that the presence of nature improves parent-child relationships indeed echoed findings from research on the restorative qualities of green spaces (Coley et al, 1997; Faber Taylor and Kuo 2011; Wells, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Barriers to exercise such as boredom, deconditioning, pain, and movement difficulties can be further compounded by environmental factors such as location and weather. 7,8 To promote participation in exercise at sufficient dose to maintain or improve aerobic performance, there is a need to explore novel approaches to exercise prescription and the environment in which it is conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Applying wearable cameras is a recent method to investigate travelling and health behaviour. One could also calculate the time spent engaged in those activities by increasing the capture rate of the camera (Kelly et al 2014;Sawyer et al 2018). Wearable cameras have been shown to be a suitable instrument to measure different kinds of physical activities (Kelly et al 2011), as well as everyday activities (Wang and Smeaton 2013).…”
Section: Introductionmentioning
confidence: 99%